In Situ Patterning Perovskite Quantum Dots by Direct Laser Writing Fabrication - Zhan, Wenjie; Meng, Linghai; Shao, Chendi; Wu, Xian-gang; Shi, Kebin; Zhong, Haizheng (ACS photonics, 2021)
Perovskite quantum dots have been attractive building blocks for novel photonic devices development, where patterning is usually one of the most critical steps. We report on the combination of in situ fabrication and direct laser writing based on a 405 nm nanosecond laser, which provides an efficient and simple scheme for patterning perovskite quantum dots during the formation process. The as-fabricated gamma phase CsPbI3 quantum dots patterns show bright photoluminescence emission with a quantum yield up to 92%. By varying the key parameters of the direct laser writing, a minimum line width of 900 nm was achieved. A light-emitting optical grating with a period of 4 μm was fabricated and its polarization and structural color characteristics were discussed. The reported approach offers a route for fabricating patterned perovskite quantum dots with designed structures for photonic applications including micro-LED display, anticounterfeiting, and nanolasers.